2006
DOI: 10.1021/ie050818z
|View full text |Cite
|
Sign up to set email alerts
|

PρT Measurements and Equation of State (EoS) Predictions of Ester Lubricants up to 45 MPa

Abstract: New experimental densities in the compressed liquid state are reported for pentaerythritol tetrapentanoate (PEC5) over the temperature range of 278.15−353.15 K and for pressures up to 45 MPa. Density values (99 experimental data) have been measured with a high-pressure vibrating tube densimeter. A correction factor that was due to the viscosity of the sample was applied to the experimental density values. These data were used to determine isothermal compressibilities, isobaric thermal expansion coefficients, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
80
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(88 citation statements)
references
References 49 publications
8
80
0
Order By: Relevance
“…This behavior has been documented in different papers, mainly by Randzio et al [1][2][3][4][5] and in papers referencing newly measured thermophysical properties of fluids [6,7]. The isobaric expansivity ˛, defined by:…”
Section: Introductionmentioning
confidence: 87%
“…This behavior has been documented in different papers, mainly by Randzio et al [1][2][3][4][5] and in papers referencing newly measured thermophysical properties of fluids [6,7]. The isobaric expansivity ˛, defined by:…”
Section: Introductionmentioning
confidence: 87%
“…9 it can be concluded that a high a/b ratio could be obtained with lubricants of low internal pressure and thermal pressure coefficient, and high scaling coefficient and isothermal compressibility. In Table 4 the a/b, a p and j T values at T = 313.15 K and p = 50 MPa of six ILs, squalane, and four pentaerythritol ester lubricants are presented, together with the scaling exponent c. For all the fluids, the a p and j T values were determined through fits of a Tait equation to the experimental density data of the literature [49][50][51][52][53][54][67][68][69][70] and by obtaining the corresponding analytical derivatives. Roland et al [63] determined the c value for squalane, [C 8 C 1 im]BF 4 , and [C 8 C 1 im]PF 6 , whereas Fandiño et al [71] evaluated the c exponents for the pentaerythritol esters and Pensado et al [65] calculated those of the other ILs.…”
Section: Pressure Viscosity Coefficientsmentioning
confidence: 99%
“…The effect of viscosity on the density measurements made by U-tube densimeters has been extensively studied experimentally [11][12][13][14][15][16][17][18][19] and, recently, the increasing interest in high viscosity liquids has intensified the awareness in this effect [15][16][17][18]. However, to the knowledge of the authors, no theoretical study has been published.…”
Section: Introductionmentioning
confidence: 99%